Unenlightened Economism: The Antecedents of Bad Corporate Governance and Ethical Decline - Huehn, Matthias Philip (Journal of business ethics, 2008)
The paper expands on Goshal’s criticism of what management as a scientific discipline teaches and the effects on managerial and societal ethics. The main argument put forward is that the economisation of management has a detrimental effect on the practice of management and on society in large. The ideology of economism is described and analysed from an epistemological perspective. The paper argues that the economisation of management not only introduces the problems of economics (three are identified and discussed) but destroys the very essence of management because economics is focused on efficiency and management should be focused on effectiveness. What is more, the basic axioms of mainstream economics stand in stark contrast to the philosophy of the Enlightenment and therefore endanger the foundations of Western societies. Management theory (via corporate governance) is the Trojan horse carrying economism into society.